Enhancing Engagement With Socially Disadvantaged Older People in Organized Physical Activity Programs. (July 2019) - Nau, Tracy; Nolan, Genevieve; Smith, Ben J.
Background and objectives: Participation in physical activity (PA) is low among older adults in developed nations and even lower among several socially disadvantaged groups. This study aimed to identify the actions that can be taken in the promotion, design, and implementation of organized PA programs to improve engagement with socially disadvantaged and underrepresented older people. Research design and methods: Semistructured interviews were conducted with 30 community service providers and 5 focus groups with 42 older participants in existing PA programs. Data were analyzed thematically, and the PRECEDE-PROCEED model for program planning was used to broadly categorize themes. Results: Helpful strategies for addressing predisposing factors such as social anxiety and lack of confidence included user-centered program design and sensitive, informative messaging and promotion. Key enabling strategies were transport assistance and minimizing fees. Facilitating gentle entry to groups and fostering inclusion and safety were identified as valuable reinforcing strategies. Providers regarded organizational networks as beneficial for facilitating referral and addressing resource constraints. Discussion and implications: A multifactorial approach addressing a range of predisposing, reinforcing, and enabling factors is likely to be necessary to enhance engagement in organized PA by socially disadvantaged and underrepresented older people. Key factors relate to creating a positive sociocultural environment, identifying activities of interest, and enhancing ease of access.